2007
DOI: 10.1021/la0637014
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Microdomain Orientation in Block Copolymer Thin Films with Homopolymers for Lithographic Application

Abstract: Block copolymer lithography is a promising method for fabricating periodical nanopatterns of less than 20 nm by self-assembly and can be applicable for fabricating patterned magnetic media with a recording density over 1 Tb/in.2. We found a simple technique to control the orientation of cylindrical microdomains in thin films. Simply by mixing polystyrene-block-poly(methyl methacrylate) (PS-b-PMMA) diblock copolymers with the homopolymer (PS or PMMA) of the major component, we could align the cylindrical microd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 28 publications
0
43
0
Order By: Relevance
“…[11][12][13][14][15] It has been also reported that the structure of self-assembled monolayers (SAMs) of alkylsiloxanes on SiOx/Si substrate plays an important role in determining the wetting behavior of block copolymer thin films, which can be correlated to the interfacial and surface energies. 16,17 For some commercial applications, the directed self-assembly of block copolymers leading to an perpendicular microdomain orientation in thin films is desired 13,[18][19][20][21] since this enables the use of the microdomain patterns as templates and scaffolds for nanolithographic applications. 22,23 This strategy has been achieved by surface modification, 24,25 strong electric field, 26,27 and solvent annealing.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] It has been also reported that the structure of self-assembled monolayers (SAMs) of alkylsiloxanes on SiOx/Si substrate plays an important role in determining the wetting behavior of block copolymer thin films, which can be correlated to the interfacial and surface energies. 16,17 For some commercial applications, the directed self-assembly of block copolymers leading to an perpendicular microdomain orientation in thin films is desired 13,[18][19][20][21] since this enables the use of the microdomain patterns as templates and scaffolds for nanolithographic applications. 22,23 This strategy has been achieved by surface modification, 24,25 strong electric field, 26,27 and solvent annealing.…”
Section: Introductionmentioning
confidence: 99%
“…Since acetone is selective to both portion of the block copolymer, it swells into both PS and PDMS phases. The existence of acetone in both blocks balances their solubility parameters and results in a decrease in the segregation energy between PS and PDMS as described in Equation (1). On the other hand, DMF is selectively dissolved into PS block and leads to the absence of the solvent in the PDMS portion.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of ordering is not as good compared to the case of 17 nm-pitch block copolymer. This is due to the reduction in the segregation energy N to with the molecular weight as described in Equation (1). Further optimization of the process conditions for increasing the diffusivity of block polymers is necessary.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk microstructures of these materials have been well characterized using microscopy and small-angle scattering methods. However, it is well known that surface microstructure and mobility effects can differ significantly from the bulk case and will vary with depth below the surface (Kitano et al, 2007;Kawaguchi et al, 2003;Brown & Chakrabarti, 1994). The extent to which surface effects are manifested below the airpolymer interface is not well established.…”
Section: Introductionmentioning
confidence: 99%